(Im)Possíveis fontes para história da saúde no Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This study primarily aims to make the sources of the Division of Scientific Research and Documentation (DPDC) of the Paraná Health Department accessible, facilitating the consultation of the document collection. With a special focus on historical records, such as health diplomas and licenses since 1886, the research explores the evolution of health in Brazil, highlighting the relevance of document preservation for institutional identity. Besides analyzing these records, the study addresses the lack of archival policies, hindering access to documents relevant for researchers. The research examines the trajectory of health from the colonial period to the present day. This analysis is essential to understand the context in which the records were generated and the development of health in Paraná. The study's methodology is based on the analysis of historical records, especially in the books of health diplomas and licenses. The results highlight the wealth of information contained in the diploma records, providing an overview of the professional trajectory of health professionals over 96 years. In terms of conclusions, the research emphasizes the importance of document preservation not only as safeguarding but as a crucial component of institutional identity and history. It stresses the urgent need to invest in specialized personnel to ensure proper organization and efficient availability of documents. The study underlines the invaluable value of diploma records and registration books as essential sources for scientific research, significantly contributing to enriching the understanding of the history of health and health education in Paraná.
Keywords: Memória institucional; Registros históricos; Políticas arquivísticas; Saúde pública; Educação em saúde; Institutional memory; Historical records; Archival policies, Public health, Health education; CNPQ::CIENCIAS HUMANAS::HISTORIA